1999
DOI: 10.1055/s-2007-978788
|View full text |Cite
|
Sign up to set email alerts
|

The Leptin-Fat Ratio is Constant, and Leptin May be Part of Two Feedback Mechanisms for Maintaining the Body Fat Set Point in Non-Obese Male Fischer 344 Rats

Abstract: While plasma leptin and adiposity have been found to be strongly related, the specific nature of this relationship has yet to be clarified. Hence, plasma leptin and three indicators of adiposity were measured in adult male Fischer 344 rats on three different long-term diets: continuous ad libitum feeding; ad libitum feeding until early adulthood, then continuous 60% caloric restriction; and ad libitum feeding until early adulthood, then 60% caloric restriction until 16 months, then ad libitum feeding for 5 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
3
9
1
Order By: Relevance
“…Since its discovery a few years ago, serum leptin has proved to be directly related to body fat in both humans (1,2) and rats (3). This has been considered to be the main evidence that it is a white adipose tissue (WAT) messenger signalling the size of the fat store to the central nervous system, in agreement with the adipostatic theory proposed by Kennedy (4) and sustained by Hausberger's experiments (5).…”
Section: Introductionsupporting
confidence: 56%
“…Since its discovery a few years ago, serum leptin has proved to be directly related to body fat in both humans (1,2) and rats (3). This has been considered to be the main evidence that it is a white adipose tissue (WAT) messenger signalling the size of the fat store to the central nervous system, in agreement with the adipostatic theory proposed by Kennedy (4) and sustained by Hausberger's experiments (5).…”
Section: Introductionsupporting
confidence: 56%
“…Leptin is a hormone whose plasma levels are directly related to the amount of body fat [41,42]. Leptin, therefore, informs the central nervous system of the fat store size, which is in agreement with the adipostatic theory proposed by Kennedy [43].…”
Section: Discussionsupporting
confidence: 65%
“…Greenberg et al . have suggested that, under controlled conditions, the plasma‐leptin‐to‐body‐fat ratio is constant for a particular mammalian strain, independent of dietary history (38). In this study, significant positive correlations were also observed between the serum leptin concentration and the sum of the fat tissue weights in male, female, and OVX rats ( , and ).…”
Section: Discussionmentioning
confidence: 99%